Implementasi Penggunaan Permainan Celengan Huruf Terhadap Kemampuan Mengenal Huruf di PAUD - Muzfirah, Suci; Faziyah, Muidatul; Mahmud, Hamid; Nafis, Rukhiyah (Iftitiah: Jurnal Ilmiah Pendidikan Islam Anak Usia Dini, 2025)
At the age of 0-6 years it is a fundamental period because the child's further development is determined by the various kinds of stimulus given. Related to children's development in terms of language, there are two children's language development, namely spoken language and written language. Education for early childhood aims to provide supervision, care, guidance, create and provide learning and play experiences, identify deviations from an early age and carry out early intervention, develop children's abilities. In this research the method used is descriptive method. Descriptive method can be interpreted as a problem-solving procedure that is investigated by describing/describing the state of the subject/object of research of a person, institution, community and others at present based on facts or as they are. The results of the study in group A RA Baiturrahmah, namely through interviews with core teachers and accompanying teachers, children aged 4-5 years (group A) are said to be able to recognize letters well if the child is able to show a letter, and if the child is able to read a word well in reading books and outside the school environment. Based on the results of the research and discussion on "Implementation of the Use of Letter Piggy Bank Games on the Ability to Recognize Letters in Early Childhood Education", it can be concluded that (1) Before carrying out the stimulus activities in Group A there were still many who could not distinguish the shapes of letters that were almost the same and also distinguish the sound of letters that are almost the same. (2) Stimulating activities in letter recognition by using the letter piggy bank media. In this activity Group A was able to recognize letters well. (3) The constraints that exist when the learning process uses piggy bank letters include classroom management, children's independence and lack of learning stimulus.